Playfair Cipher Algorithm in Learning Media - Subhan Hafiz Nanda Ginting; Muhammad Rhifky Wayahdi; Surya Guntur (Politeknik Ganesha Medan, 2022)
The level of security and confidentiality of information / data becomes very important in the era of increasingly sophisticated and developing technology. Cryptographic methods can be one solution to overcome problems in the level of security and confidentiality of information. However, knowledge about cryptography is still a lot of audiences who do not know and understand its use in securing the secrets of information, for that we need an application which presents a learning media that is expected to help provide knowledge from cryptography. This study implements a learning media application that discusses a Playfair Cipher classic cryptographic method, a cryptographic technique that encrypts bigrams using a matrix table consisting of 25 letters in it, text that can be encrypted in the form of alphabet letters on the system that has been tested. The results of the encryption and decryption of the text do not have spaces or symbols in it, the application of playfair cipher cryptographic learning media is aimed at computer students as a tool to better understand the playfair cipher cryptographic material.